2010
DOI: 10.1073/pnas.1003292107
|View full text |Cite
|
Sign up to set email alerts
|

Satellite-based global-ocean mass balance estimates of interannual variability and emerging trends in continental freshwater discharge

Abstract: Freshwater discharge from the continents is a key component of Earth's water cycle that sustains human life and ecosystem health. Surprisingly, owing to a number of socioeconomic and political obstacles, a comprehensive global river discharge observing system does not yet exist. Here we use 13 years (1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006) of satellite precipitation, evaporation, and sea level data in an ocean mass balance to estimate freshwater discharge into the global o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
104
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(114 citation statements)
references
References 41 publications
(54 reference statements)
3
104
3
Order By: Relevance
“…These processes enhanced rock weathering during the last century (Probst et al, 1994). Intuitively, this fact suggests an increased export of carbon by rivers, but whether the global river runoff has increased is uncertain (Dai et al, 2011;Syed et al, 2010). The construction of dams around the world has caused a substantial fraction of exported sediment to be impounded in recent decades (Chen, 2002;Syvitski et al, 2005).…”
Section: Future Changes In Carbon Fluxesmentioning
confidence: 99%
“…These processes enhanced rock weathering during the last century (Probst et al, 1994). Intuitively, this fact suggests an increased export of carbon by rivers, but whether the global river runoff has increased is uncertain (Dai et al, 2011;Syed et al, 2010). The construction of dams around the world has caused a substantial fraction of exported sediment to be impounded in recent decades (Chen, 2002;Syvitski et al, 2005).…”
Section: Future Changes In Carbon Fluxesmentioning
confidence: 99%
“…Even wellmonitored countries have sparsely distributed networks, thus limiting current understanding of water losses along river courses, habitat changes, and flood risk (3,4). Satellites, in contrast, provide spatially dense coverage globally, attracting calls for a global river discharge mapping capacity from space (5)(6)(7)(8)(9)(10). However, previous efforts to estimate river discharge from remotely sensed observations have all required inclusion of some form of ancillary ground-based information, such as gauge measurements, bathymetric surveys, and/or calibrated hydrology models that are simply unavailable for most of the planet (11)(12)(13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…Mounting evidence has suggested that climate and its change has played an important role in controlling the water cycle by changes in evaporation, transpiration, and runoff (McCabe, 2002;Hamlet et al, 2007;Syed et al, 2010;Wang and Hejazi, 2011;Chien et al, 2013;Hegerl et al, 2014;Huntington and Billmire, 2014;McCabe and Wolock, 2014;Sun et al, 2014). Also, climate can exert a dominant control on vegetation structural and phenological characteristics through variations in air temperature, precipitation, solar radiation, wind, and CO 2 concentration (Nemani et al, 2003;Harding et al, 2011;Wang et al, 2014;Zhang, F. et al, 2014;.…”
Section: Introductionmentioning
confidence: 99%